(untitled) (Colloquia Comparativa Litterarum, 2025)
The aim of this article is to draw parallels between two French-language writers: Senegalese Mariama Bâ (1929–1981) and Swiss-born Anne-Lise Grobéty (1949–2010), through their convergent appropriations of dialogicity. More specifically, the paper examines the generational dialogues staged through the prism of an explicit feminine claim, women’s fellowship, “sororities” in writing, as well as certain interactions between women’s writing and the readership in their novels. The adopted perspective, which is both comparative and gendered, makes it possible to sketch out a similar vision of female empathy and solidarity in the body of work of the two women writers.